Hubungan antara amalan TQM dengan kepuasan kerja guru Sekolah Menengah di Daerah Tanah Merah - Rosmawati, Affendi (2009)
The purpose of this study was to identify the relationship between TQM practices and teacher's job satisfaction. The TQM practices such as customer focus, board of school management commitment, continuous improvement and teacher involvement. The objectives of this study are to investigate (a) the differences between job satisfaction and gender, (b) the differences between job satisfaction and academic qualification, (c) the differences between job satisfaction and the position in school, (d) the differences between job satisfaction and teaching experience, (e) the relationship between customer focus and job satisfaction, (f) the relationship between board of school commitment and job satisfaction, (g) the relationship between continuous improvement and job satisfaction and (h) the relationship between teacher involvement and job satisfaction. 285 teachers from twelve secondary schools have been chosen randomly as respondent. The study instrument used to measure TQM practices were taken from the questionaires by Das, Paul and Swierczek (2008). Eventhough these questionaires contain ten dimensions, but there are only four used as construct which are consistently used to explain the TQM practices. This instrument used five-point Likert-type scale. To measure teacher job satisfaction, Teaching Satisfaction Scale (TSS) questionaires by Chung-Lim Ho and Wing-Tung Au were used in this study. T-Test and One Way ANOVA were used to test the differences, whereas Pearson Correlation were used to test the relationship between TQM practices variables and job satisfaction. The findings revealed that the job satisfaction mean score for female teacher is more than male teacher. The findings shows that the differences between job satisfaction and the gender and the differences between job satisfaction and the position in school. For academic qualification and teaching experience, the findings shows that there was no differences for job satisfaction. Lastly, the findings shows that there were positive and significant relationship among job satisfaction and customer focus, board of school management commitment, continuous improvement and teacher involvement